(Z)-2-Methoxy-N-[(5-nitrothiophen-2-yl)methylidene]aniline - Kaynar, Nihal Kan; Gumus, Sumeyye; Agar, Erbil; Büyükgüngör, Orhan; Yavuz, Metin (Wiley-Blackwell, 2012)
The dihedral angle between the benzene and thiophene rings in the title compound, C12H10N2O3S, is 27.94 (13)degrees. An intermolecular C-H center dot center dot center dot pi interaction contributes to the stability of the crystal structure.
WOS: 000301059200044
PubMed: 22347015